Improvement of well-being in cancer patients by yoga training (Medical Journal of Indonesia, 2018)
Background: Cancer patients frequently suffer from a reduced physical activity. Non-pharmacological interventions, such as yoga, provide opportunities to deal with these symptoms. The aim of this study is to evaluate the effect of yoga on the well-being of cancer patients.Methods: Between 2015 and 2017, we analyzed the effects of yoga on the well-being of cancer patients. Fifty-one patients received yoga training specifically designed to address cancer-related problems. Before the start (SoS) and after the end (EoS) of training, the WHO-5 well-being index was used to evaluate patients’ perception.Results: WHO-5 scores significantly improved from 47.1±21.4 at SoS to 69.7±15.1 at EoS. Patients in the middle age group (EoS–SoS: 28.0±20.6) showed a significantly higher benefit (p<0.005) compared with age groups <40 years (EoS–SoS: 10.7±15.4) and>60 years (EoS–SoS: 16.0±12.1). Patients with low initial scores benefited most from yoga.Conclusion: Our study showed that yoga training under experienced supervision could serve as a beneficial complementary treatment in cancer patients. Best effects were observed in patients with highly reduced well-being and40–60-year-old patients.